Respuesta :

Answer:

detail shown in step by step below

Step-by-step explanation:

y = mx + b               m: slope  b: y intercept

m = (y'-y) / (x'-x)

(28)  (0,2) (3,0)  m= -2/3          y < -2/3 * x +2

        (0,-3) (3,0) m= 1               y > x - 3

(29)  (-2,0) (-3,-2)  m= 2              y < 2x + 4

         (-4,-1) (0,-2)   m= - 1/4         y ≥ (- 1/4) * x -2

(30)   (0,3) (3,0)  m= -1                  y > - x + 3

         (0,0) (1,3)  m= 3                  y ≥ 3x

(31)    (0,4) (4,0)  m= -1                   y ≤ - x + 4

         (3,3) (2,-1)  m= 4                   y ≥ 4x - 9

          while                                    x < 2